The Methodist church in Poland - Michalak, Ryszard, author.
1 online resource.
Keywords: "This book explores the development and activity of the Methodist Church in Poland, focusing on the political conditions under which it functioned after 1945. In particular it considers the role of party and state power, and the nature and impact of religious policy towards the Church. The chapters touch on organizational issues, missionary activity, and key figures in the recent history of the Church. Drawing on more than twenty years of research on Polish methodism and the increasing availability of archival material, this volume will be of interest to scholars of religion, politics, and history"--